Digitoxin Inhibits Epithelial-to-Mesenchymal-Transition in Hereditary Castration Resistant Prostate Cancer - Pollard, Bette S.; Suckow, Mark. A.; Wolter, William R.; Starr, Joshua M.; Eidelman, Ofer; Dalgard, Clifton L.; Kumar, Parameet; Battacharyya, Sharmistha; Srivastava, Meera; Biswas, Roopa; Wilkerson, Matthew D.; Zhang, Xijun; et al. (Frontiers in Oncology, 2019)
Castration Resistant Prostate Cancer (CRPC) is thought to be driven by a collaborative mechanism between TNF/NFB and TGFsignaling, leading to inflammation, Epithelial-to-Mesenchymal-Transition (EMT), and metastasis. Initially, TGFis a tumor suppressor, but in advanced metastatic disease it switches to being a tumor promoter. TGFBR2 may play a critical role in this collaboration, as its expression is driven by NFB and it is the primary receptor for TGF. We have previously reported that the cardenolide drug digitoxin blocks TNF/NFB-driven proinflammatory signaling. We therefore hypothesized that digitoxin might break the collaborative process between NFB and TGF by also inhibiting expression of TGFBR2. We therefore tested whether TGF-driven EMT and resulting metastases would be suppressed. Here we show, in vitro, that digitoxin inhibits NFB-driven TGFBR2 expression, as well as Vimentin and SNAI1 expression, while E-cadherin expression is elevated. In vivo, in a syngeneic, immune competent rat model of metastatic CRPC, we show that digitoxin also suppresses Tgfbr2 expression, as well as expression of other genes classically driven by NFkB, and of multiple EMT genes associated with metastasis. Concurrently, digitoxin suppresses tumor growth and metastasis in these animals, and prolongs survival. Gross tumor recurrence following tumor resection also appears prevented in ca 30% of cases. While the existence of a collaboration between NFB and TGFto drive EMT and metastasis has previously been appreciated, we show here, for the first time, that chronic, low concentrations of digitoxin are able to block CRPC tumor progression, EMT and the ensuing metastatic disease.